Genomic and Transcriptomic Study for Screening Genes Involved in the Limonene Biotransformation of Penicillium digitatum DSM 62840 - Zhang, Lu-Lu; Huang, Wen; Zhang, Ying-Ying; Fan, Gang; He, Jin; Ren, Jing-Nan; Li, Zhi; Li, Xiao; Pan, Si-Yi (Frontiers in Microbiology, 2020)
α-Terpineol has been widely used in daily chemical, pharmaceutical, food and flavor industries due to its pleasant odor with high economic value and pharmacological action. Our previous study showed that Penicillium digitatum DSM 62840 was an efficient biocatalyst for the transformation of limonene to α-terpineol. Thus, it was meaningful to explore the genome features and the gene expression differences of strain DSM 62840 during limonene biotransformation, and the detailed bioconversion pathways. In this study, the functional genes related to limonene bioconversion were investigated using genome and transcriptome sequences analysis. The results showed that the P. digitatum DSM 62840 genome was estimated to be 29.09 Mb and it encoded 9,086 protein-encoding genes. The most annotated genes were associated to some protein metabolism and energy metabolism functions. When the threshold for differentially expressed genes (DEGs) was set at two-fold ratio, a total of 4, 128 and 4, 148 DEGs were identified in P_L_12h (limonene-treated condition) compared with P_0h (blank) and P_12h (limonene-untreated blank), respectively. Among them, the expression levels of genes involved in the biosynthesis of secondary metabolites, energy metabolism and ATP-binding cassette (ABC) transporters were significantly altered during the biotransformation. And the reliability of these results was further confirmed by qantitative real-time polymerase chain reaction (RT-qPCR). Moreover, we found that the enzyme participated in limonene biotransformation was inducible. This enzyme was located in the microsome, and it was inhibited by cytochrome P450 inhibitors. This indicated that the cytochrome P450 may be responsible for the limonene bioconversion. Several differentially expressed cytochrome P450 genes were further identified, such as PDIDSM_85260 and PDIDSM_67430, which were significantly up-regulated with limonene treatment. These genes may be responsible for converting limonene to α-terpineol. Totally, the genomic and transcriptomic data could provide valuable information in the discovery of related-genes which was involved in limonene biotransformation, pathogenicity of fungi, and investigation of metabolites and biological pathways of strain DSM 62840.